2020
DOI: 10.1136/jitc-2020-001689
|View full text |Cite
|
Sign up to set email alerts
|

Serum CD73 is a prognostic factor in patients with metastatic melanoma and is associated with response to anti-PD-1 therapy

Abstract: BackgroundInhibitors of immune checkpoint programmed cell death protein 1 (PD-1) receptor on T cells have shown remarkable clinical outcomes in metastatic melanoma. However, most patients are resistant to therapy. Production of extracellular adenosine, via CD73-mediated catabolism of AMP, contributes to suppress T-cell-mediated responses against cancer. In this study, we analyzed the expression and activity of soluble CD73 in sera of patients with melanoma undergoing anti-PD-1± cytotoxic T-lymphocyte-associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 32 publications
0
18
0
1
Order By: Relevance
“…15 Interestingly, we have recently demonstrated the soluble form of CD73 as predictive peripheral blood biomarker of response to nivolumab or pembrolizumab in patients with metastatic melanoma. 21 The serum contains multiple forms of CD73: the soluble CD73 which derives from the cleavage of the cell-membrane anchored CD73, and a form expressed on exosomes. Importantly, it is known that cancer exosomes carry CD73, which is enzymatically active in producing adenosine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Interestingly, we have recently demonstrated the soluble form of CD73 as predictive peripheral blood biomarker of response to nivolumab or pembrolizumab in patients with metastatic melanoma. 21 The serum contains multiple forms of CD73: the soluble CD73 which derives from the cleavage of the cell-membrane anchored CD73, and a form expressed on exosomes. Importantly, it is known that cancer exosomes carry CD73, which is enzymatically active in producing adenosine.…”
Section: Discussionmentioning
confidence: 99%
“…To measure the activity of CD73 in purified exosomal samples, we evaluated the AMPase hydrolysis using multiple reaction monitoring mass spectrometry (MRM-MS), as described before. 21 A total of 5 µg of exosomes proteins in 50 µL total volume of PBS were incubated at 37°C for 10 min, and then treated or not with CD73 inhibitors for 30 min at 37°C. Specifically, we used 5' α,β-methylene-ADP (APCP; Sigma-Aldrich) (100 µM) or the anti-human CD73 mAb (Clone 7G2; Thermo Fisher Scientific) (5 µg/mL).…”
Section: Cd73 Enzymatic Activity Measurementmentioning
confidence: 99%
“…[ 29 ]. In some instances, enzymes involved in the hydrolysis of extracellular nucleotides have become reliable indicators for monitoring disease [ 30 , 31 ]. These enzymes include members of the ENTPD family, which hydrolyze ATP into AMP, and CD73, which hydrolyses AMP to adenosine [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several serum markers associated with melanoma survival or response to therapy, including lactate dehydrogenase and CD73, have been described, but few studies have successfully identified and validated serum or CSF markers of melanoma-associated IMD, which occurs in over 50% of melanoma patients [ 99 , 100 , 101 ]. The use of cytopathology to detect whole circulating melanoma cells in CSF has been described in the diagnosis of leptomeningeal disease; however, the application of this technique may be limited by its specificity, as patients without circulating melanoma cells may have IMD [ 102 ].…”
Section: Biomarkers Of Intracranial Metastases In the Context Of Specific Primary Cancersmentioning
confidence: 99%